Light in the dark: distinct effects of dimethyl fumarate on different T‐cell subsets in psoriasis treatment. (1st March 2021) - Mostafa, A.; Murata, T.; Kabashima, K.
Abstract: Linked Article: Sulaimani et al . Br J Dermatol 2021; 184 :495–503 .